BUMDES SAWIT MANDIRI: INOVASI KELEMBAGAAN DESA DALAM MEWUJUDKAN KESEJAHTERAAN BERKELANJUTAN - Lina Warniati (DEVELOPMENT: Journal of Community Engagement, 2025)
This study examines the role of BUMDes Sawit Mandiri in Cibubukan Village, Aceh Singkil, as a concrete effort to promote community empowerment and economic independence at the village level. Emerging from a context of stagnant socio-economic conditions, low village revenue, and underutilized assets, BUMDes was established to manage local potential—particularly palm oil plantations in a professional, participatory, and sustainable manner. Employing a qualitative case study approach, data were collected through in-depth interviews, direct observations, and document analysis. The findings reveal that community participation is a key determinant of BUMDes’ success, although challenges persist due to limited information access, residents’ work constraints, and insufficient communication between local government and the community. The study also highlights that the success of BUMDes is not solely measured by its economic outcomes but also by its ability to foster collective awareness, strengthen accountability, and reinforce local social structures. Therefore, BUMDes Sawit Mandiri functions not only as a village business unit but also as a transformative social institution with the potential to achieve local economic sovereignty when managed under the principles of participation, transparency, and community empowerment.